Refreshing Self-Reliance - Sam Hamilton (NANO, 2016)
“Refreshing Self-Reliance” is a random quote generator, populated with pithy aphorisms from Ralph Waldo Emerson’s 1841 essay “Self-Reliance.” When you hit the ↻ or “Refresh” button in your browser, a new statement from Emerson’s essay appears. Underneath this statement are two white hyperlinks (“Introduction” and “Non-Randomized Reflections”) and one smaller gray hyperlink (“Works Cited, Consulted, and Considered”). The “Introduction” hyperlink brings you to these introductory remarks to “Refreshing Self-Reliance,” while the “Non-Randomized Reflection” allows you to read “Refreshing Self-Reliance” in a more linear/narrative manner, i.e. “non-randomized,” and the “Works Cited, Consulted, and Considered” takes you to a MLA-formatted end-of-text citation page. All of this constitutes the “first layer” of “Refreshing Self-Reliance.”